Risk factors associated with hydrocephalus persistence after posterior fossa tumors resection: https://doi.org/10.59156/revista.v36i04.593 - Cicutti, Santiago Ezequiel; Cuello, Francisco; Gromadzyn, Guido (Revista Argentina de Neurocirugía, 2023)
Background. Posterior fossa tumors are the most frequent central nervous system neoplasms in the pediatric population and a frequent cause of hydrocephalus. The objective of this study is to analyze the risk factors associated with hydrocephalus after posterior fossa tumors resection in a pediatric population. Methods. A retrospective observational study was conducted on pediatric patients who underwent posterior fossa tumor resection in a single hospital. Potential pre- and post-operative risk factors were analyzed. The need for definitive shunt placement to treat hydrocephalus at 6 months after tumor resection was considered as the outcome variable. Results. Univariate analysis identified multiple significant risk factors. However, only 3 factors remained in the multivariate model: extent of resection (subtotal: OR 7.86; partial: OR 20.42), postoperative infection (OR 17.31), and absence of postoperative outflow of the fourth ventricle (OR 4.29). This model showed good predictive capacity (AUC: 0.80, Sensitivity 80.5%, Specificity 76.3%). Conclusion. Preoperative endoscopic third ventriculostomy did not reduce the incidence of postoperative hydrocephalus. The extent of tumor resection, presence of postoperative infection, and obstruction of fourth ventricle outflow were the most important risk factors for the requirement of a definitive shunt system after posterior fossa tumor resection. This could influence treatment decisions in this group of pediatric patients.